Two-photon excited fluorescence (TPEF) may be useful to identify macrophage subsets based on their metabolic activity and cellular responses in atherosclerotic plaques. (September 2020) - Borowczyk, Coraline; Laroche-Traineau, Jeanny; Brevier, Julien; Jacobin-Valat, Marie-Josée; Marais, Sébastien; Gerbaud, Edouard; Clofent-Sanchez, Gisèle; Ottones, Florence
Abstract: Background and aims: Atherosclerosis is characterized by the formation of lipid plaques within the arterial wall. In such plaques, the massive and continuous recruitment of circulating monocyte-derived macrophages induces inflammation, leading to plaque destabilization and rupture. Plaque vulnerability is linked to the presence of (i) a large lipid core that contains necrotic, "foamy" macrophages (FMs), (ii) a thin fibrous cap that cannot limit the prothrombotic lipid core, and potentially (iii) an imbalance between inflammatory and immunoregulatory macrophages. These opposite macrophage functions rely on the use of different energy pathways (glycolysis and oxidative phosphorylation, respectively) that may lead to different levels of the auto-fluorescent cofactors nicotinamide adenine dinucleotide (NADH) and flavin adenine dinucleotide (FAD). We hypothesized that high-resolution two-photon excited autofluorescence (TPEF) imaging of these cofactors may be used to monitor the metabolic activity and cellular responses of macrophages in atherosclerotic plaques. Methods: Different models of human FMs were generated by exposure to acetylated or oxidized low-density lipoproteins (LDL), with/without human carotid extract (CE). Their phenotype and optical properties were compared with those of extremely polarized macrophages, inflammatory M1 (MLPS+IFNγ ) and immunoregulatory M2 (MIL4+IL13 ). Results: These FM models displayed an intermediate phenotype with low levels of M1 and M2 "specific" markers. Moreover, the NADH and FAD autofluorescence profiles of FMoxLDL ± CE cells were significantly distinct from those of M1 and M2 macrophages. Conclusions: TPEF imaging may be useful to follow the metabolic activity and cellular responses of the different macrophage subtypes present in atherosclerotic plaques in order to detect vulnerable areas. Graphical abstract: Image 1 Highlights: Foamy macrophages express pro-inflammatory and anti-inflammatory markers at low level. The human pathophysiological foamy macrophage model is optically distinguishable from M1 and M2 macrophages. Label-free two-photon imaging is a highly sensitive and non-destructive tool to assess macrophage metabolic functions. The optical redox ratio could be used as a new label-free imaging tool to identify vulnerable atheroma plaques.